UJI MEDIA PEMELIHARAAN Mesocyclops aspericornis (Daday) DARI BERBAGAI KOTORAN TERNAK UNTUK MENINGKATKAN PRODUKSI COPEPODIT - Munawir Sazali; Muhammad Ali Azis Hasan Rizki (Scripta Biologica, 2017)
Natural predators of mosquito larvae are known and used as biological control of the mosquito larvae of Aedes aegypti, one of them is a copepod, Mesocyclops aspericornis. The effectiveness of the biological control of Aedes aegypti larvae requires an efficient method to rear Mesocyclops aspericornis copepodite. This research aimed to determine the feasibility of various organic manures, i.e., cow dung (RKS), goat manure (RKK), and marmot manure (RKM) as aquaculture media of M. aspericornis copepodite. This experiment was conducted in the laboratory using a post-test only control group design. The group design consisted of 5 concentrations of 0%, 25%, 50%, 75%, and 100%, each with three replicates for each organic manure media. The statistical analyses showed each organic manure medium was not significantly affecting (p = 0.521) the copepod aquaculture. However, the concentration of the manure has a significant correlation with the number of copepodites raised (p = 0.001). Games-Howell test suggested the most effective manure concentration to rear M. aspericornis copepodite was 25%.